Dánarhlutfall heilablóðfallssjúklinga á Sjúkrahúsi Reykjavíkur á árunum 1996-1997 - Jón Hersir Elíasson; Einar M. Valdimarsson; Finnbogi Jakobsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: The purpose of this study was to describe case-fatality after acute stroke at the Reykjavik Hospital. A study describing the outcome of stroke patients in an Icelandic population has not been published before. Material and methods: A prospective hospital-based stroke registry has been conducted at the Reykjavik Hospital since January 1996. Patients with ischemic stroke and intracerebral hemorrhage were included in this study but patients with transient ischemic attack (TIA), subarachnoid hemorrhage and hemorrhage due to hereditary cystatin C amyloid angiopathy were excluded. We describe the severity of symptoms at stroke onset, length of hospital stay and outcome. Results: In 1996 and 1997 a total of 377 events were registered. Ischemic stroke was diagnosed in 88% and hemorrhagic stroke in 12%. The case-fatality was 17%, 71% of the patients were discharged home and 12% to nursing care. The average length of hospital stay was 28.7 days (95% CI 24.1-33.3) and 63% of patients were treated at the stroke unit. Eighty-five percent of patients could have been treated at the stroke unit but 15% needed intensive care unit (ICU) or other intensive medical care. Conclusions: Case-fatality was lower and the pro-portion of patients discharged home was higher than we have seen reported in foreign studies. Stroke may be a less severe disease in Iceland than in other Western countries. Tilgangur: Tilgangur rannsóknarinnar var að kanna fjölda og afdrif sjúklinga með heilablóðfall á Sjúkrahúsi Reykjavíkur. Skoðuð var hlutdeild heilablóðfallseiningar í þjónustu við þennan sjúklingahóp og athugaðar ástæður þess að sjúklingar lögðust ekki inn á heilablóðfallseiningu. Ekki hafa áður verið birtar niðurstöður rannsókna á Islandi sem lýsa afdrifum sjúklinga með heilablóðfall í stóru þýði. Efniviður og aðferðir: Skráðar voru upplýsingar um sjúklinga með heilablóðfall á Sjúkrahúsi Reykjavíkur á:árunum 1996 og 1997 jafnóðum og ...